Biomechanical report for the IAAF World Indoor Championships 2018 shot put men - Thomas, A.; Dinsdale, A.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2019)
The men`s shot put took place during the daytime of Saturday 3rd March. Coming into the final, Tomáš Stanek from the Czech Republic was the favourite as he held the world leading throw in 2018. However, the world outdoor gold medallist Tomas Walsh from New Zealand took a commanding lead in the first round with a throw of 22.13 m, which he later bettered in the sixth round with a Championship record measured at 22.31 m. None of the other athletes could respond to Walsh`s impressive world leading throws and as such he secured the gold medal. The silver medal was hotly contested between David Storl from Germany and Stanek. Remarkably, both athletes threw the same distance in the fourth round measured at 21.44 m, although neither athlete threw further and as such the silver medal was decided based on David Storl`s superior second-best throw measured at 21.18 m. Hence, Stanek was awarded the bronze medal due to his slightly inferior second-best throw measured at 21.12 m.